Plasma Proteomics Characteristics of Subclinical Vitamin E Deficiency of Dairy Cows During Early Lactation - Qian, Weidong; Yu, Hongyi; Zhang, Cuiyu; Zhang, Hongyou; Fu, Shixin; Xia, Cheng (Frontiers in Veterinary Science, 2021)
Vitamin E (VE) is an essential fat-soluble nutrient for dairy cows. VE deficiency leads to immune suppression and oxidative stress, and increases the susceptibility of cows to reproductive disorders in the early postpartum period. However, studies on plasma proteomics of VE deficiency have not been reported so far. Therefore, the purpose of this study was to understand the changes of blood protein profile in cows with subclinical VE deficiency in early postpartum period. In this study, plasma protein levels of 14 healthy cows (>4 ug/mL α-tocopherol) and 13 subclinical VE deficient cows (2-3 ug/mL α-tocopherol) were analyzed by Tandem Mass Tag (TMT). The results showed that there were 26 differentially expressed proteins in the plasma of cows with subclinical VE deficiency compared with healthy controls. Twenty-one kinds of proteins were down-regulated and 5 kinds up-regulated, among which 8 proteins in Protein-protein interactions (PPT) network had direct interaction. These proteins are mainly involved in MAPK signaling pathway, pantothenic acid and coenzyme A biosythesisi, PPAR signaling pathway and Glycosyl phosphatidy linositol-anchor biosynthesis. The top-four differentially expressed proteins in PPI (APOC3, APOC4, SAA4, PHLD) and one important protein (VNN1) by literature review were further verified by ELSA and Western blot. The expression levels of APOC3, VNN1 and SAA4 were significantly lower than those of healthy controls by ELSA . VNN1 was significantly lower than those of healthy controls by Western blot. VNN1 is closely related to dairy cow subclinical VE deficiency and can be a potential biomarker. It lays a foundation for further research on the lack of pathological mechanism and anti-oxidative stress of VE.